Design and implementation of an open-loop dual-axis active solar tracking system with precision angle controller - Ahmad, Salsabila (2012)
Malaysia is moving forward in fully utilizing its Renewable Energy resources, due to its long term benefits. The challenge in electricity generation from solar technology is that it is still economically expensive due to higher equipment cost and low efficiency, while solar tracking devices add more to the cost. The objectives of this research are to come out with a design of an open-loop dual axis solar tracker with one degree angle controller and compare the power produced from the solar tracker with horizontally fixed panel and solar tracker with ten degree angle controller. Overall, the significant contribution of this research is in terms of the system’s structural design, where the structure was designed to accommadate and maneuver two heavy solar panels with minimal power consumption. The main component of this solar tracker is a Programmable Logic Controller with Real Time Clock that controls the motors and other electromechanical devices. The total daily energy consumed for the driving system is 6.66 x 10-2 Wh. In terms of improving the energy collected, this research focuses on producing a maximum energy possible by minimizing the solar incidence angle on the solar panel based on the programming that controls the panel’s angle to face the sun by one degree precision. The experiment shows a comparison of performance of a two-axis tracking system compared to a fixed horizontal panel. The results data provide evidence that the energy produced from the system on a clear and sunny day is higher by 58.74% and 58.42% compared to a fixed horizontal panel for one and ten degree angle controller,respectively. In comparison of one-degree and the ten-degree angle controllers, onedegree angle controller gives better results between 1% to 48%, than ten-degree angle controller, with a more significantly higher percentage during the late afternoon. Finally, the results provide a conclusion that two-axes solar tracking system in this climate is relevant due to a high energy gain for a clear and sunny day. On the whole, this research should help to flourish research in Renewable Energy efforts particularly solar, in Malaysia, as the implementation of the system locally can help to maximize the efficiency and minimize the cost of solar power generation.